1983
DOI: 10.1139/g83-067
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome distribution between two restitution nuclei in a cell following colchicine treatment

Abstract: 1983. Chromo\ome distribution between two restitution nuclei in a cell following colchicine treatment. Can. J. Genet. Cytol. 25: 437 -445. Roots of Zea maj.s L., ,Secwle c-ereale I,., Vicin jirba, L . , Alliutn c.ep(r L . , and Hordeum ~lirlgrrre L, were treated with colchicine. C-metaphases were observed in cells which had chromosomes present in two distinct groups. not the typical single group. Chromosome distribution into two groups was not followed by chromatid segregation: instead, the chromosomes underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Another microtubule and mitotic inhibitor, colchicine, is known to cause binucleate cell formation in plant cells as a result of distributive cmitoses, which allocate chromosomes into two groups in the apparent absence of a functional mitotic spindle apparatus (4, 13). Davidson et al (4) demonstrated that such anomalous mitoses can result in aneuploidy, thereby having genetic consequences similar to those of benzimidazole compounds, including benomyl and its active hydrolysis product, MBC. Hence, the morphological and genetic effects of benomyl on polyploid brewing yeast cells reported in this study appear similar to the reported effects of colchicine on plant cells.…”
Section: Resultsmentioning
confidence: 99%
“…Another microtubule and mitotic inhibitor, colchicine, is known to cause binucleate cell formation in plant cells as a result of distributive cmitoses, which allocate chromosomes into two groups in the apparent absence of a functional mitotic spindle apparatus (4, 13). Davidson et al (4) demonstrated that such anomalous mitoses can result in aneuploidy, thereby having genetic consequences similar to those of benzimidazole compounds, including benomyl and its active hydrolysis product, MBC. Hence, the morphological and genetic effects of benomyl on polyploid brewing yeast cells reported in this study appear similar to the reported effects of colchicine on plant cells.…”
Section: Resultsmentioning
confidence: 99%
“…When studying the meristems treated by colchicine for a long period of time, it could be observed that some cells presented irregularly shaped polyploid nuclei in interphase, never seen in meristems untreated with colchicine. These polyploid nuclei were named restitution nuclei (Davidson, Pertens & Zhao, 1983). They are derived from the c-mitoses, after the decondensation of their high condensed chromosomes and the reformation of the nuclear envelope (Nagl, Pohl & Radler, 1985).…”
Section: The Formation Of Restitution Nucleimentioning
confidence: 99%